LC-MS-Based Metabolomic Study of Oleanolic Acid-Induced Hepatotoxicity in Mice - Feng, Hong; Wu, Ying-Qiu; Xu, Ya-Sha; Wang, Ke-Xin; Qin, Xue-Mei; Lu, Yuan-Fu (Frontiers in Pharmacology, 2020)
Oleanolic acid (OA), a natural triterpenoid, is widely used hepatoprotective drug in China and has potential in the treatment of anti-tumor. However, it has been reported that OA can cause hepatotoxicity following high doses or long-term use, nevertheless, the mechanism remains unclear. To better explore possible mechanisms of OA-induced hepatotoxicity, we examined metabolic changes in liver of mice administered a high or low dose of OA for 4 days using UHPLC- Q Exactive Orbitrap-MS technique. We found that altered bile acids metabolism, amino acids metabolism and energy metabolism could be at least partly responsible for OA hepatotoxicity. Further targeted metabolomics experiments using UHPLC-TSQ-MS/MS confirmed and quantified that unconjugated bile acids were decreased and conjugated bile acids were increased after OA administration. These results demonstrate that OA can disturb the bile acid hemostasis, which is the main contributor of OA hepatotoxicity.